The Effect of Service Quality and Price on Customer Satisfaction and Customer Loyalty at Apotek XYZ Bekasi Area - Izul Ariesta; Wahono Sumaryono; Deriawan Deriawan (PT Mattawang Mediatama Solution, 2023)
Health is an important need for society. The increasing social status of the community at this time affects the demands of the community for the quality of services of health service providers which are also increasing. This requires health service providers to always improve the quality of their services to be even better. Currently many places are starting to provide health services. More health service providers means more competitors are emerging. Facing competition in the health service sector, health service providers are required to always provide good service to improve the quality of their services so that patient trust is always given to health service providers so that it can have an impact on patient satisfaction and patient loyalty. The health service provider must be able to provide information and patient needs so that the patient's wishes can be fulfilled and increase patient satisfaction. The purpose of this research is to analyze the quality of service and price that can affect customer satisfaction and loyalty The research was conducted at the XYZ pharmacy with three hundred and thirtyeight respondents. Two independent variables in this study were service quality and price. seen to determine the relationship with the dependent variable, namely customer loyalty with the intervening variable is customer satisfaction. The results of the analysis of the data obtained are the quality of service has an effect on customer satisfaction and customer loyalty, customer satisfaction has an effect on customer loyalty.